PENGARUH DANA PIHAK KETIGA (DPK), NON PERFORMING FINANCING (NPF) DAN PENEMPATAN DANA PADA BANK INDONESIA TERHADAP PROFITABILITAS BANK UMUM SYARIAH PERIODE 2011-2014 - SUBARKAH, IDRUS (Jurnal Akuntansi AKUNESA, 2016)
The purpose of this study was to analyze the relationship and influence The Effect Of Third Party Funds, Non Performing Financing and Placement Funds in Bank Indonesia on Profitability Syariah Bank. This analysis will be used as a reference both for owners, investors, customers, and other stakeholders. Of all the population there are 9 syariah bank that have met the criteria for the research samples during 2011-2014. Data used in the study in the form of financial reports that has been published on the official website of the Bank Indonesia and official website on syariah bank. This type of research uses quantitative approach with multiple linear regression method. These results indicate that Non Performing Financing affect on Profitabilty Syariah Bank. Third Party Funds and Placements Funds in Bank Indonesia does not affect on Profitabilty Syariah Bank.   Keywords: Third Party Funds, Non Performing Financing, Placement Funds in Bank Indonesia and Profitability.